2011
DOI: 10.1039/c0dt00690d
|View full text |Cite
|
Sign up to set email alerts
|

Apatite germanates doped with tungsten: synthesis, structure, and conductivity

Abstract: High oxygen content apatite germanates, La 10 Ge 6-x W x O 27+x , have been prepared by doping on the Ge site with W. In addition to increasing the oxygen content, this doping strategy is shown to result in stabilisation of the hexagonal lattice, and yield high conductivities. Structural studies of La 10 Ge 5.5 W 0.5 O 27.5 show that the interstitial oxygen sites are associated to a different degree with the Ge/WO 4 tetrahedra, leading to five coordinate Ge/W and significant disorder for the oxygen sites assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
4
18
0
Order By: Relevance
“…Appearance of the characteristic Raman band around 650 cm À1 corresponding to the stretching mode of GeeO in GeO 5 unit experimentally supports the existence of the interstitial oxygen bound to Ge in Sr 2 (Mg 1Àx Ga x )Ge 2 O 7þ0.5x with x ¼ 0.2 and 0.5 as shown in Fig. S6 [21,22].…”
Section: Resultssupporting
confidence: 61%
“…Appearance of the characteristic Raman band around 650 cm À1 corresponding to the stretching mode of GeeO in GeO 5 unit experimentally supports the existence of the interstitial oxygen bound to Ge in Sr 2 (Mg 1Àx Ga x )Ge 2 O 7þ0.5x with x ¼ 0.2 and 0.5 as shown in Fig. S6 [21,22].…”
Section: Resultssupporting
confidence: 61%
“…However, lanthanum germanate apatites often encounter the downside of GeO 2 volatilization at high temperatures, leading to the formation of another conducting phase, La 2 GeO 5 . It has been reported in the literature that a triclinic apatite phase exists in the La‐Ge‐O phase diagram . Leon‐Reina et al .…”
Section: Introductionmentioning
confidence: 99%
“…13,15 It has been reported in the literature that a triclinic apatite phase exists in the La-Ge-O phase diagram. 16,17 Leon-Reina et al found that La 9.33+x (GeO 4 ) 6 O 2+3x/2 samples with a composition of 0.19≤x≤0.27 were marked with hexagonal symmetry, while those with a higher La content of 0.33≤x≤0.42 exhibited a triclinic cell, which leads to more strongly bound oxygen, and results in reduced conductivity. 2 Nakayama et al reported that the electrical conductivities of La x (GeO 4 ) 6 O 1.5xÀ12 depend on the La content; they found that La 9.0 (GeO 4 ) 6 O 1.5 had the highest conductivity among various La x (GeO 4 ) 6 O 1.5xÀ12 apatites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where A are rare-earths or alkaline-earths and B is Si or Ge. Apatites contain several cation acceptor sites leading to a wide range of substitutional possibilities [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67] with ion mobility modified by varying cation type and proportions.…”
Section: Problem Statementmentioning
confidence: 99%